Comparative performance analysis of one rank cuckoo search technique based optimization for automatic generation control of interconnected power systems - Manoharan, N.; Sekhar Dash, Subhransu; Sivalingam, Raghuraman; P. R., Dheeraj (International Journal of Engineering and Technology, 2017)
This paper presents a one rank cuckoo search optimization technique is proposed to design classical PID Controllers for Automatic Generation Control (AGC) of interconnected power systems. This method is proposed based on the original cuckoo search method. It was found in original cuckoo search the convergence speed is comparative lesser in reaching optimal solutions. To overcome the above mentioned problem one rank cuckoo search algorithm has been proposed which uses a bound by best solution technique to get the valid dimension so as to improve the system performance and rate of convergence. The proposed approach is applied to a four area hydro-thermal system in which area-1 and area-2 are steam reheat power plant and area-3 and area-4 are hydro power plant. The controller gains are derived using original cuckoo search and one rank cuckoo search methods. The superiority of the proposed approach is compared with the results obtained with original cuckoo search algorithm.